PEMBERDAYAAN KELOMPOK SIAGA BENCANA BERBASIS MASJID DI LERENG MARAPI NAGARI CANDUANG KABUPATEN AGAM SUMATERA BARAT - Aidil Alfin; Ali Rahman (Turast: Jurnal Penelitian dan Pengabdian, 2022)
Indonesia is one of the countries that has the intensity of frequent natural disasters. Almost all areas experienced these natural disasters. According to the records of the National Disaster Management Agency (BNPB) in 2017 alone, there were 884 natural disasters in Indonesia. Floods and landslides are the most common natural disasters compared to other disasters. One of the areas that are prone to disasters is Nagari Canduang Koto Laweh on the slopes of Mount Merapi, West Sumatra, the community is not yet aware of disasters, so assistance is needed for this community. Assistance is carried out with a mosque approach where the mosque is used as a centre for mitigation propaganda and KSB activities. The results of this assistance have given birth to a disaster preparedness village, where the community is starting to be disaster-savvy, disaster-responsive and resilient.